Analisis Personal Branding Content Creator TikTok @claramonica - Claudia Dinata; Sisca Aulia (Kiwari, 2022)
TikTok social media has a big impact on everyone's way of interacting and accessing information. This study uses Personal Branding Theory to find out personal characteristics that make interest to form positive perceptions in the form of interesting content as a medium of entertainment for today's trends. This study aims to analyze the personal branding content creator of TikTok @claramonica. This study uses a qualitative approach with a case study method on the use of the TikTok application. The data collection carried out is observation, documentation, and interview techniques. The results of this study indicate that the age difference in the use of the TikTok application will affect the personal branding of the informants. The use of the TikTok application to increase self-confidence, can develop skills, creativity, characteristics, and build a public image.Media sosial TikTok memberikan dampak besar pada bagaimana orang berinteraksi dan mengakses informasi. Penelitian ini menggunakan Teori Personal Branding untuk mengetahui karakter pribadi yang membentuk minat untuk membentuk persepsi positif berupa konten yang menarik sebagai media hiburan untuk tren masa kini. Penelitian ini bertujuan untuk menganalisis personal branding content creator TikTok @claramonica. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus terhadap penggunaan aplikasi TikTok. Pengumpulan data dilakukan dengan observasi, studi dokumentasi, dan wawancara. Hasil penelitian ini menunjukkan bahwa perbedaan usia dalam penggunaan aplikasi TikTok berkontribusi pada pembentukan personal branding narasumber. Penggunaan aplikasi TikTok digunakan untuk meningkatkan rasa percaya diri yang dimiliki, dapat mengembangkan skill, kreativitas, ciri khas, dan membangun citra public.